Pengaruh intellectual capital dan pengungkapan corporate social responsibility terhadap kinerja perusahaan (studi pada perusahaan high profile yang terdaftar di bursa efek indonesia) - Arbain Arbain; Yana Ulfah; Ledy Setiawati (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
Purpose of this study was to examine the effect of intellectual capital and corporate social responsibility as the independent variables on the performance of companies on a high profile company listed on the Indonesia Stock Exchange as the dependent variable. The population in this study is a company that includes high profile companies listed on the Indonesia Stock Exchange. The sampling technique in this study using purposive sampling method and acquired 11 companies that met the study criteria and obtained 44 research data for 4 years from 2012 to 2015. Results in this study indicate that the positive effect of intellectual capital but did not significantly affect the performance of the company, while corporate social  responsibility  positive  effect  but  significant effect  on  the  company's performance on a high profile company listed on the Indonesia Stock Exchange.Keywords: Intellectual Capital and Corporate Social Responsibility